Analyzed Quality of Senior High School Biology Olympiad Questions at West Sumatera, Riau, Jambi, and Bengkulu in 2018 - Eka Aghnia Syarif; Syamsurizal Syamsurizal (Bioeducation Journal, 2019)
The aim of this study to determine the quality of items in terms of analysis : 1) the validity of content and empirical, 2) reliability, 3) level of difficulty, 4) distinguishing features, and 5) the function of detractors. This research is a descriptive study. The sample was a set of biology olimpic question for senior high school year 2018/209 in West Sumatera, Riau, Jambi, and Bengkulu. Quantitative analysis was performed by using Anates, while for the qualitative analysis carried out by the study table. Based on the results of data analysis, the result for the review of aspects : 1) the validity of the content 52.5% are invalid matter, 2) reliability, the test has a value of 0.6 belong to the category enough, 3) the level of difficulty, 1,6% classified as very easy matter, 1,6% easy, 36.6% about the medium, 41,6% about the difficult, and 18.3% about the very difficult, 4) different power, 65% of matter which is classified as very bad, 28.5% about the relatively ugly, 6.6% about enough, and 0% items good, 5) function options, for options that are not qualified humbug is 36.6% and the quality is 63,3%. It can be concluded that the end of the senior high school biology olympiadquestions at West Sumatera, Riau, Jambi, and Bengkulu in 2018 through the 4.0 version of Anates program not meet both criteria.